Determination of Volatile Compounds in Raw Milk with Mastitis - Nükhet Nilüfer Demirel Zorba; Seda Özdikmenli Tepeli; Musa Yalman (Food Science and Engineering Research)
Mastitis is a prevalent and economically significant disease in dairy cattle, affecting milk composition and quality. Subclinical mastitis (SCM) is more common and often asymptomatic. It can alter the chemical and cellular composition of milk, making it more difficult to process and potentially affecting the quality of dairy. This study aimed to investigate the volatile compounds present in raw cow's milk using Solid Phase Microextraction (SPME) and Gas Chromatography-Mass Spectrometry (GC-MS). Milk samples were collected from various producers in Çanakkale, Biga and Yenice districts in Türkiye. From these, 10 samples that tested positive in the California Mastitis Test (CMT) were selected for analysis. A total of 49 volatile compounds were determined, including hydrocarbons (9), alcohols (4), aldehydes (3), ketones (7), acids (4), esters (11), terpenes (1), aromatic compounds (5), nitrogenous compounds (1), and other compounds (4). The most prevalent volatile components were butanoic acid, hexanoic acid, octanoic acid, and n-decanoic acid, which contribute to rancid and cheesy flavors in the milk. Other notable compounds detected included acetoin, various ketones, terpenes like d-limonene, and alcohols such as 3-methyl-1-butanol. The presence of these compounds is largely attributed to the metabolic activities of lactic acid bacteria and the degradation of fatty acids. The findings indicate that SCM significantly alters the volatile compound profile of milk, leading to the development of off-flavors that could impact the sensory quality of dairy products. The aim of this study is to provide information about the chemical changes that may occur in raw milk associated with SCM and to emphasize the importance of monitoring milk quality to ensure consumer safety and uphold high standards in dairy product quality.